Pengaruh Faktor Harga, Fasilitas, Lokasi dan Kualitas Pelayanan Terhadap Keputusan Konsumen untuk Menginap di Toraja Heritage Hotel - Adolfina Ro’son; Abedneigo. C. Rambulangi; Mey Enggane Limbongan (Transformasi: Journal of Economics and Business Management, 2023)
The purpose of this study is to determine whether there is an effect of price, facilities, location, quality of service on consumer decisions at Toraja Heritage Hotel. Data collection procedures from this research are observation, questionnaire, and documentation. The data analysis technique is quantitative with multiple linear regression tests. The conclusion of this study is that the variable facilities have no effect on consumer decisions and the variables price, location, and service quality have an effect on consumer decisions in Toraja Heritage Hotel.